Epigenetic reprogramming at estrogen-receptor binding sites alters 3D chromatin landscape in endocrine-resistant breast cancer - Joanna Achinger-Kawecka (Nature Portfolio, 2020)
Endocrine therapy resistance occurs often in estrogen receptor positive (ER+) breast cancer. Here, the authors find that 3D epigenome remodelling at ER-bound enhancer-promoter interactions is a key mechanism underlying endocrine resistance.